Powered by www.myengg.

com

TRANSFORMATIONS
PREVIOUS EAMCET BITS
1.

cos x
= λ ⇒ tan ( x − y ) tan y =
cos ( x − 2y )

[EAMCET 2009]

1+ λ
1− λ
λ
2)
3)
1− λ
1+ λ
1+ λ
Ans: 2
cos ( x − 2y ) 1
= , using component to and dividendo:
Sol.
λ
cos x
1− λ
tan ( x − y ) tan y =
1+ λ
1)

2.

λ
1− λ

cos A cos 2A cos 4A......cos 2n −1 A =

sin 2n A
2n sin 2n A
2)
2n sin A
sin A
Ans: 1
1
Sol.
[ 2sin A cos A cos 2A cos 4A....]
2sin A
1)

cos ⎡⎣( 2n −1 A ) ⎤⎦ =
3.

4)

[EAMCET 2009]

3)

2n sin A
sin 2n A

4)

sin A
2 sin 2n A
n

sin ( 2n A )
2n sin A

If α + β+ γ = 2θ, then cos θ + cos ( θ − α ) + cos ( θ − β ) + cos ( θ − γ ) =

[EAMCET 2008]

α
β
γ
α
β
γ
cos sin
2) 4 cos cos cos
2
2
2
2
2
2
α
β
γ
3) 4sin sin sin
4) 4sinαsinβsinγ
2
2
2
Ans: 2
Sol. cos θ + cos ( θ − α ) + cos ( θ − β ) + cos ( θ − γ )
1) 4sin

β−γ
⎛ 2θ − α ⎞
⎛α⎞
⎛ 2θ − β − γ ⎞
= 2 cos ⎜
⎟ cos ⎜ ⎟ + 2 cos ⎜
⎟ cos
2
2
⎝ 2 ⎠
⎝2⎠


α
β−γ
⎛β+γ ⎞
⎛α⎞
= 2 cos ⎜
⎟ cos ⎜ ⎟ + 2 cos cos
2
2
⎝ 2 ⎠
⎝2⎠
α⎡
β+γ
β−γ⎤
α
β
γ
= 2 cos ⎢cos
+ cos
= 4 cos cos cos

2⎣
2
2 ⎦
2
2
2
4.

sin A + sin B = 3 ( cos B − cos A ) ⇒ sin 3A + sin 3B =

1) 0
2) 2
Ans: 1
Sol. Given sin A + sin B = 3 ( cos B − cos A )

3) 1

1

Powered by www.myengg.com

[EAMCET 2007]
4) – 1

Powered by www.myengg.com

Transformation
⎛ 3⎞
⎛ 3⎞
⎛1⎞
⎛1⎞
⎜⎜ 2 ⎟⎟ cos A + sin A ⎝⎜ 2 ⎠⎟ = cos B ⎜⎜ 2 ⎟⎟ − sin B ⎝⎜ 2 ⎠⎟




π⎞
π⎞


⇒ cos ⎜ A − ⎟ = cos ⎜ B + ⎟
6⎠
6⎠


A = − B ⇒ sin 3A + sin 3B = 0

5.

A + C = 2B ⇒

1) cotB
Ans: 4
A+C
Sol.
=B
2

cos C − cos A
sin A − sin C
2) cot2B

[EAMCET 2005]
3) tan 2B

A+C
A−C
2sin
sin
cos C − cos A
2
2 = tan B
=
sin A − sin C 2 cos A + C sin A − C
2
2
2
2
A + B = C ⇒ cos A + cos B + cos 2 C − 2 cos A cos B cos C =
6.
1) 1
2) 2
3) 0
Ans: 1
Sol. A + B = C
cos 2 A + cos 2 B + cos 2 C = 1 + cos ( A + B ) cos ( A − B ) + cos 2 C

4) tan B

[EAMCET 2005]
4) 3

= 1 + cos C ⎡⎣ cos ( A − B ) + cos ( A + B ) ⎤⎦
= 1 + cos ( 2 cos A cos B )

cos 2 A + cos 2 B + cos 2 C − 2 cos A cos Bcos C = 1
⎛ Β + 2C + 3A ⎞
⎛A−B⎞
7.
In ΔABC , cos ⎜
⎟ + cos ⎜
⎟=
2


⎝ 2 ⎠
1) – 1
2) 0
3) 1
Ans: 2
⎛ π + C + 2A ⎞
⎛ A−B⎞
Sol. cos ⎜
⎟ + cos ⎜

2


⎝ 2 ⎠
⎛ 2π − B + A ⎞
⎛ A−B⎞
= cos ⎜
⎟ + cos ⎜
⎟=0
2


⎝ 2 ⎠
8.
cos α,sin ( β − γ ) + cos β.sin ( γ − α ) + cos γ.sin ( α − β ) = ………..
1) 0
Ans: 1
Sol. Σ cos α sin ( β − γ )

2) 1/2

3) 1

[EAMCET 2004]

4) 2

[EAMCET 2003]

4) 4cosαcosβcosγ

= Σ cos α ( sin β cos γ − cos β sin γ ) = 0
sin 47° − sin 25° + sin 61° − sin11° =
1) cos 7°
2) sin 7°
Ans: 1
Sol. sin 47° − sin25° + sin 61° − sin11°

9.

[EAMCET 2003]

3) 2 cos 7°

2

Powered by www.myengg.com

4) 2 sin 7°

Powered by www.myengg.com

Transformation
= sin 47° + sin 61° − ( sin 25° + sin11° )
= 2sin 54° cos 7° − 2sin18° cos 7°

10.

Sol.
11.

Sol.

12.

Sol.

13.

Sol.

⎛ 5 +1
5 −1 ⎞
= 2 cos 7° ⎜⎜

⎟ = cos 7°
4 ⎟⎠
⎝ 4
If A + B + C = 270°, then cos2A + cos2B + cos2C + 4sinAsinBsinC = ….
1) 0
2) 1
3) 2
4)3
Ans: 2
cos 2A + cos 2B + cos 2C = 1 − 4 sin A sin Bsin C
(or) Put A = B = C= 90°
cos 2 76° + cos 2 16° − cos 76° cos16° =
1
1
3
2) 0
3) −
1)
4)
2
4
4
Ans: 4
1
cos 2 76° + 1 − sin 2 16° − ( 2 cos 76° cos16° )
2
1
= 1 + cos ( 76° + 16° ) cos ( 76° − 16 ) − ( cos 92° + cos16° )
2
1
1
1 3
= 1 + cos 92° − cos 92° − =
2
2
4 4
3
=
4
3
π⎞

cos 2 ⎜ ( 2k − 1) ⎟ =

12 ⎠

k =1
1
1
3
3) –
4)
1) 0
2)
2
2
2
Ans: 4
π


cos 2 + cos 2
+ cos 2
12
12
12
1 + cos 30° 1 + cos 90° 1 + cos150° 3
+
+
=
2
2
2
2
p+q
⎛π θ⎞
, then cot ⎜ + ⎟
If cos ecθ =
p−q
⎝ 4 2⎠
p
q
1)
2)
3) pq
4) pq
q
p
Ans: 2
1
p + q 1 + sin θ p
=

=
sin θ p − q 1 − sin θ q
⎛π

⎛π θ⎞
1 − cos ⎜ + θ ⎟
2sin 2 ⎜ + ⎟
⎝2
⎠=p⇒
⎝ 4 2⎠ = p

⎛π
⎞ q
⎛π θ⎞ q
1 + cos ⎜ + θ ⎟
2 cos 2 ⎜ + ⎟
⎝2

⎝ 4 2⎠

3

Powered by www.myengg.com

[EAMCET 2003]

[EAMCET 2002]

[EAMCET 2002]

[EAMCET 2001]

Powered by www.myengg.com

Transformation

14.

p
⎛π θ⎞
∴ cot ⎜ + ⎟ =
p
⎝ 4 2⎠
If sin α + sin β = a, cos α + cos β = b, then sin ( α + β ) =
1) ab

2) a + b

3)

2ab
a − b2
2

[EAMCET 2000]

4)

2ab
a + b2
2

Ans: 4
Sol. sin α + sin β = a;cos α + cos β = b
⎛ α +β ⎞
⎛ α −β ⎞
⎛ α +β ⎞
⎛ α −β ⎞
2sin ⎜
⎟ cos ⎜
⎟ = a; 2 cos ⎜
⎟ cos ⎜
⎟=b
⎝ 2 ⎠
⎝ 2 ⎠
⎝ 2 ⎠
⎝ 2 ⎠
⎛ α+β⎞ a
∴ tan ⎜
⎟=
⎝ 2 ⎠ b
⎛ α+β⎞
2 tan ⎜

⎝ 2 ⎠ = 2ab
sin ( α + β ) =
⎛ α + β ⎞ a 2 + b2
1 + tan 2 ⎜

⎝ 2 ⎠
cos ( θ1 − θ2 )
15. If tan θ1 = k cot θ2 , then
=
cos ( θ1 − θ2 )

1+ k
1− k
2)
1− k
1+ k
Ans: 1
cos ( θ1 − θ2 ) cos θ1 cos θ2 + sin θ1 sin θ2
Sol.
=
cos ( θ1 + θ2 ) cos θ1 cos θ2 − sin θ1 sin θ2
1 + tan θ1 tan θ2 1 + k

=
1 − tan θ1 tan θ2 1 − k
1)

3)

k +1
k −1

555

4

Powered by www.myengg.com

[EAMCET 2000]

4)

k −1
k +1